Lernen gestalten Beiträge der empirischen Forschung zu Innovationen in Schule und Universität - Haas, Mareike; Krieg, Maria (Universitätsverlag Göttingen, 2021)
Questions of digitization and the increasing heterogeneity of learners are just two of the central challenges that schools and universities currently face. Educational institutions are therefore undergoing constant change in order to ensure and develop the quality of education. The resulting innovation processes can be very diverse and relate to both structural conditions and social interactions in the teaching situation. This book deals with these changes (innovations) in teaching and learning in a variety of ways and addresses structural development measures as well as individual conditions of learning. Reference is made to both the school and the university context.